"It's a really grey area": An exploratory case study into the impact of the Jackson Reforms on organised insurance fraud. (December 2017) - Davies, John
Abstract: The Jackson Reforms were designed to address the mounting cost of UK civil justice by reducing personal injury claims' costs, yet the government presented them as part of wider counter insurance fraud initiatives. This case study utilises counter fraud practitioner interviews and industry data to explore the reforms' impact on organised insurance fraud. The study highlights how a market of supplier-induced demand may exist in the personal injury market whereby fraud need only be committed by one actor to have a financial benefit to other parties. Such a situation causes difficulties identifying actual fraud, particularly as actors may unconsciously participate. Despite this the insurance industry has already publicised its own conclusions and supports further reforms to the sector. This study will argue that without further examination of the Jackson Reforms subsequent reforms may inadvertently serve to shift fraud into new areas and cause further challenges for counter fraud practitioners.